Diagenetic Modifications and Reservoir Heterogeneity Associated with Magmatic Intrusions in the Devonian Khyber Limestone, Peshawar Basin, NW Pakistan. (3rd May 2021) - Shah, Mumtaz M.; Afridi, Saifullah; Khan, Emad U.; Rahim, Hamad Ur; Mustafa, Muhammad R.
Abstract : In the present study, an attempt has been made to establish the relationship between diagenetic alterations resulting from magmatic intrusions and their impact on the reservoir properties of the Devonian Khyber Limestone (NW Pakistan). Field observations, petrographic studies, mineralogical analyses, porosity-permeability data, and computed tomography were used to better understand the diagenetic history and petrophysical property evolution. Numerous dolerite intrusions are present in the studied carbonate successions, where the host limestone was altered to dolomite and marble, and fractures and faults developed due to the upwelling of the magmatic/hydrothermal fluids along pathways. Petrographic studies show an early phase of coarse crystalline saddle dolomite (Dol. I), which resulted from Mg-rich hydrothermal fluids originated from the dolerite dykes. Coarse crystalline marble formed due to contact metamorphism at the time of dolerite emplacement. The second phase of dolomitisation (Dol. II) postdates the igneous intrusions and was followed by dedolomitisation, dissolution, and cementation by meteoric calcite. Stable isotope studies likewise confirm two distinct dolomite phases. Dol. I exhibits more depleted δ 18 O (-15.8 to -9.1‰ V-PDB) and nondepleted δ 13 C (-2.05 to +1.85‰ V-PDB), whereas Dol. II shows a relatively narrow range of depleted δ 18 O (-13.9 to -13.8‰) signatures and nondepleted δ 13 C (+1.58 to +1.89‰ V-PDB). Dolomitic marble shows a marked depletion in δ 18 O and δ 13 C (-13.7 to -8.5‰ and -2.3 to 1.95‰, respectively). The initial phase of dolomitisation (Dol. I) did not alter porosity (5.4-6.6%) and permeability (0.0-0.1 mD) with respect to the unaltered limestone (5.6-6.9%; 0.1-0.2 mD). Contact metamorphism resulted in a decrease in porosity and permeability (3.3-4.7%; 0.1 mD). In contrast, an increase in porosity and permeability in Dol. II (7.7-10.5%; 0.8-2.5 mD) and dolomitic marble (6.6-14.7%; 8.2-13.3 mD) is linked to intercrystalline porosity and retainment of fracture porosity in dolomitic marble. Late-stage dissolution and dedolomitization also positively affected the reservoir properties of the studied successions. In conclusion, the aforementioned results reveal the impact of various diagenetic processes resulting from magmatic emplacement and their consequent reservoir heterogeneity.